MEMBANGUN GURU PENDIDIKAN AGAMA ISLAM (PAI) YANG PROFESSIONAL - Hasibuan, Armyn (AIN Padangsidimpuan, 2014)
AbstractTeachers are as educators and teachers who are responsible for the smooth implementation of education and teaching in schools where he served as an educator and instructor. Professionally applied in the teaching-learning process aimed at achieving a target teachers with National educational purposes hopefully enlighten and matured learners.Developing teachers as professional instructors, teachers are required to understand the things that are philosophical, conceptual, and technical support matters concerning the implementation of the teaching-learning process in education. Moreover, the most important is that berkepribadian noble self competency as a model for learners.To be a teacher of Islam, that professional education should have a capital base that is competent personal profile mastering the intricacies of education and a life of service, sacrifice sincerely. Integration of Islamic education in developing highly professional teachers expects learners to be able to support the child's character and preserve local cultural wisdom as the universality of Islamic education.Kata kunci: membangun, guru pendidikan agama Islam dan profesional